La poesia di Ovidio letteratura e immagini - Chiara Renda (Testi: Antichità, Medioevo e Umanesimo, 2020)
Within the vast Ovidian bibliography, taking the opportunity provided by the celebrations of the Bimillenary of the poet's death (17-2017), the volume aims at offering a useful tool to deepen, in a diachronic and synchronic perspective, not only the multifarious virtues of Ovid's poetry, his extraordinary Alexandrian ars, the stages of his Reception starting from antiquity, but also - if not above all - an undisputed and in some ways unreachable quality of the Ovidian language and style: the disruptive icastic strength, the ability to employ, like few others, the images in the construction of the poetic text, of its narrative plots, of its elegant refinement, of its effectiveness in the reader's Reception. The versatility of Ovid's poetry, the transversality of its readings and of its possible reuse throughout the history of western culture are confirmed by the coexistence, within the volume, of contributions ranging from classical to modern and contemporary literatures, from archeology to Art history, from philosophy to music.